(untitled) (International Seven Journal of Health Research, 2024)
The diagnosis of acute cholecystitis is based on the signs and symptoms presented by the patient and also on imaging tests. As the clinical picture can have different presentations depending on the patient’s health conditions and age, sometimes confirmation is totally dependent on radiology reports, which in this case are examiner-dependent, which is inherently prone to human error and can lead to incorrect diagnoses. We analyzed the history contained in the medical records of a patient who was admitted to the emergency department complaining of abdominal pain and a letter written by her doctor, recommending emergency surgery to treat acute cholecystitis. New tests were carried out, which ended up ruling out the previous diagnosis, and the surgical procedure revealed a perforated peptic ulcer, which led to cholecystitis, and, overlapping, both diagnoses made the case unusual and atypical in presentation.